THE IMPORTANCE OF EXPRESSIVE VOCABULARY IN TEACHING THE RUSSIAN LANGUAGE (American Journal of Technology and Applied Sciences, 2023)
This article examines the features of expressive vocabulary in the aspect of teaching Russian as a foreign folk colloquial speech, folk colloquial speech, connotation. In many modern and classical works, it is emphasized that "the expressive function is focused on the expression of the subjective aspects of a person's perception of the real world", and subjective perception, as is known, is involved in the formation of a conceptual and linguistic picture of the human world. In turn, the linguistic picture of the world is reflected in the language and concepts (concepts) that a person operates with in his language (and speech) activity.